2004
DOI: 10.1074/jbc.m313348200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and Reactions of Ferritin with DNA

Abstract: Ferritin, normally considered a cytoplasmic iron-storage protein, is also found in the nuclei of some cells. There is no current agreement about its function(s) in this environment. Proposals include DNA protection, provision of iron to nuclear enzymes, and regulation of transcription initiation, but evidence for these functions is scanty. We have shown previously that H-ferritin subunits can be cross-linked to chromosomal DNA in vivo ( The sensitivity of this conversion to glycerol suggests that DNA is nicked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 50 publications
2
63
0
Order By: Relevance
“…A wide range of nucleic acid sizes (lengths from short oligonucleotides to several thousand nt/bp 18,19 ) and structures (single-stranded, duplex, triplex 20 and quadruplex 21 nucleic acids as well as small circular DNAs 22 ) are compatible with the assay. Under favorable conditions, the distribution of proteins between several nucleic acid molecules can be monitored within a single solution 18,23 , as can the presence of complexes differing in protein stoichiometry and/or binding site distribution 7,24 . Proteins ranging in size from small oligopeptides to transcription complexes with M r ≥ 10 6 can give useful mobility shifts 25,26 and the assay works well with both highly-purified proteins and crude cell extracts 27 .…”
Section: Advantages and Limitations Of Emsamentioning
confidence: 99%
“…A wide range of nucleic acid sizes (lengths from short oligonucleotides to several thousand nt/bp 18,19 ) and structures (single-stranded, duplex, triplex 20 and quadruplex 21 nucleic acids as well as small circular DNAs 22 ) are compatible with the assay. Under favorable conditions, the distribution of proteins between several nucleic acid molecules can be monitored within a single solution 18,23 , as can the presence of complexes differing in protein stoichiometry and/or binding site distribution 7,24 . Proteins ranging in size from small oligopeptides to transcription complexes with M r ≥ 10 6 can give useful mobility shifts 25,26 and the assay works well with both highly-purified proteins and crude cell extracts 27 .…”
Section: Advantages and Limitations Of Emsamentioning
confidence: 99%
“…This places the H-subunit rich ferritins in a strategic position to ward off possible oxidative onslaughts to DNA or, alternatively, to donate iron for enzyme activity and possibly the nicking of double stranded DNA that could result in relaxation of superhelical stress (Surguladze et al, 2004). It was shown that not only does H-subunit rich ferritin form a stable complex with DNA (Surguladze et al, 2004), but that DNA also contains specific iron-binding sites (Thompson et al, 2002).…”
Section: Ferritin In Cellular Organellesmentioning
confidence: 99%
“…It was shown that not only does H-subunit rich ferritin form a stable complex with DNA (Surguladze et al, 2004), but that DNA also contains specific iron-binding sites (Thompson et al, 2002).…”
Section: Ferritin In Cellular Organellesmentioning
confidence: 99%
“…The ethyl acetate and methanol extracts showed lower protection. Surguladze et al 28 also reported the scission of supercoiled DNA strand to nicked circular form by free radicals. The rate of nicking correlated with the iron content and was strongly inhibited by radical scavengers and chelators.…”
mentioning
confidence: 99%